2011
DOI: 10.1093/eurpub/ckr072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of a smoke-free home initiative in Rotherham, a deprived district in Northern England

Abstract: The Rotherham initiative succeeded in creating smoke-free homes. The results should help those planning similar initiatives. Important points include that: many participants had already instituted some rules regarding smoking at home; whether and how to include households that are already smoke-free; risk of fire and concern with house hygiene are important motivations; those living in smokers' homes may lack power to initiate smoke-free rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…A more recent review of interventions to create smoke-free homes during pregnancy or the neonatal period, typically based on counseling, was inconclusive due to poor study quality and the heterogeneity of outcomes reported [50]. Allmark and colleagues [51] reported evaluation results from an intervention similar to the one reported here, in which families who signed up for the program received a booklet and support materials. Although limited by no comparison group and a modest response rate, they found that among households that permitted some smoking at home before the initiative, about 78% became smoke-free after receiving the intervention program.…”
Section: Discussionmentioning
confidence: 96%
“…A more recent review of interventions to create smoke-free homes during pregnancy or the neonatal period, typically based on counseling, was inconclusive due to poor study quality and the heterogeneity of outcomes reported [50]. Allmark and colleagues [51] reported evaluation results from an intervention similar to the one reported here, in which families who signed up for the program received a booklet and support materials. Although limited by no comparison group and a modest response rate, they found that among households that permitted some smoking at home before the initiative, about 78% became smoke-free after receiving the intervention program.…”
Section: Discussionmentioning
confidence: 96%
“…However, evidence suggests that the intervention could be directly linked to the observed decrease in asthma admissions. Firstly, an evaluation of TiRO 20 and other smoke-free home initiatives in the UK 8,9 showed that parents retain information concerning smoke-free homes, and in many cases implemented a change in their smoking behaviour. Secondly, the pro portion of children with reported second-hand smoke exposure decreased after TiRO, from 12% in 2014 to 6% in 2015 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…6 The only other national smoke-free home initiative that we are aware of involved a smoke-free home pledge approach in the USA in 2001. 7 UK regional smoke free-home programmes exist 8,9 but the effect of TiRO and other smoke-free home initiatives on childhood health out comes has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most interventions to support parents in the implementation of an SFH have aimed at strengthening the children's, rather than the parents', self-efficacy and skills, although we are aware of some exceptions [20][21][22][23]. In order to improve the parents' self-efficacy and skills, interventions for parents with a partial SFH could, for instance, make use of enactive learning [31].…”
Section: Strengthening Personal Agencymentioning
confidence: 99%
“…A potential solution is to use interventions to support parents in the implementation of an SFH. Many of the current SFH interventions are school-based and offer information, education and/or a smoke-free promise for families to sign [13][14][15][16][17][18][19][20][21][22]. In some other interventions, smoke-free home advisors provide individual coaching or community-wide SFH promotion [18][19][20][21]23,24].…”
Section: Introductionmentioning
confidence: 99%